(untitled) (Quinto Sol, 2023)
This article reconstructs a controversy that arose in the city of Buenos Aires in 1891 regarding infractions against the law on the practice of medicine, allegedly committed by two actors who specialized in the treatment of tapeworms, a foreign doctor and a healer. not graduated. Based on the examination of the sources related to that case, the text proposes a reflection on three topics. Firstly, the multiple curative offers available to address this condition are traced, since it is understood that taking these offers into consideration helps to more accurately understand the components of that controversy. Secondly, the background of the social actors involved in this conflict is documented, with the understanding that it is an illustrative case of the trajectories of many other agents in the world of health in those years. Thirdly, the discussion referring to the relationships of complementarity or negotiation established between certified medicine and its unauthorized competitors is recovered.